Gaze-direction-based MEG averaging during audiovisual speech perception - Hirvenkari, Lotta; Jousmäki, Veikko; Lamminmäki, Satu; Saarinen, Veli-Matti; SAMS, Mikko E.; Hari, Riitta (Frontiers in Human Neuroscience, 2010)
To take a step towards real-life-like experimental setups, we simultaneously recorded magnetoencephalographic (MEG) signals and subject’s gaze direction during audiovisual speech perception. The stimuli were utterances of /apa/ dubbed onto two side-by-side female faces articulating /apa/ (congruent) and /aka/ (incongruent) in synchrony, repeated once every 3 s. Subjects (N = 10) were free to decide which face they viewed, and responses were averaged to two categories according to the gaze direction. The right-hemisphere 100-ms response to the onset of the second vowel (N100m’) was a fifth smaller to incongruent than congruent stimuli. The results demonstrate the feasibility of realistic viewing conditions with gaze-based averaging of MEG signals.